PENGARUH SUKU BUNGA, PRODUKSI, DAN EKSPOR KOMODITAS KARET TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - syafira, Syarifah; suri, Putri Anggreini (LPPM Universitas Malikussaleh - Indonesia, 2025)
This research was conducted in Indonesia with the aim of analyzing the influence of interest rates, production and exports of rubber commodities on economic growth in Indonesia. The data used inthis research is time series data over 33 years, from 1990 to 2022. This data was obtained from Food and Agriculture and Word Bank, and analyzed using the Vector Error Correction Model (VECM).The research results show that in the long term interest rates and production have a negative and significant effect on economic growth in Indonesia, while rubber commodity exports have a positive and significant effect on economic growth in Indonesia. In the short term, interest rates have a negativeand significant effect on economic growth inIndonesia, while rubberproduction and exports have a positive and insignificant effect on economic growth in Indonesia.